Modelling the hydraulic characteristics of diaphragm fishways and the effects on fish habitats - Wang, Xu; Wang, Fan; Yang, Jiening; Yu, Ping (Frontiers in Environmental Science, 2022)
Diaphragm fishways are often used in fishway engineering construction. Although there are an increasing number of new types of fishways, other types of diaphragm fishways can be derived from the combination or evolution of the following three basic types of fishways: vertical slot, overflow weir and orifice. To compare the hydraulic characteristics of different foundation types of fishways, the operations of vertical slot fishways, overflow weir fishways and orifice fishways are calculated by numerical simulation, and we comprehensively compare the flow field characteristics and application scenarios of various types of fishways from the two dimensions of hydraulic characteristics and application characteristics. This paper analyses the hydraulic characteristics of the flow field, such as velocity distribution and turbulent kinetic energy, and analyses the application characteristics of the fishway from the aspects of applicable flow, favourite swimming speed range, explosive swimming speed, fish passing position, and the matching characteristics of typical target fish. It is concluded that the vertical slot fishway can be widely applied to different target fish species due to its own advantages, such as less impact from environmental conditions. The characteristics of the overflow weir fishway and orifice fishway need to be analysed in combination with the hydraulic characteristics of the fishway, the swimming ability of the target fish species and the natural environmental conditions.